The Tren dan Determinan Kepatuhan Pajak: Sebuah Literature Review atas Artikel Terindeks Scopus 2024-2025 - Oom Sri Hendari; Fitriana Fitriana; Rachmat Agus Santoso (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to map trends, determinants, and research gaps on tax compliance using a Structured Literature Review approach of 15 Scopus-indexed articles. The main problem of this study is the lack of a comprehensive synthesis that integrates research developments, determinants of tax compliance, and opportunities for further research within a structured analytical framework. The research method was carried out through article identification, variable extraction, thematic grouping, and narrative synthesis based on four main clusters: economics and regulation, psychology and behavior, technology and digitalization, and governance and trust. The results show a shift in research focus from a traditional economic approach to an integration of behavioral factors and tax digitalization. The literature synthesis indicates that tax compliance is multidimensional and influenced by the interaction between taxpayer characteristics, the quality of fiscal governance, and technology adoption. This study also identified phenomenon gaps, research gaps, and theory gaps, particularly in the context of developing countries and the MSME sector. This study concludes that there is still ample opportunity for further research to develop a more integrative and contextual model of tax compliance.